MANAGERS’ SELF-DEVELOPMENT IN THE CONTEXT OF CAREER GROWTH - Arhipova, Olga; Kokina, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Career growth or career planning is a process that a person can go through to improve their professional status. It is the process of making decisions for long term learning, to align personal needs of physical or psychological fulfilment with career advancement opportunities. In the study, the relevance of self-development of career and professional growth of managers was determined by the need to organize events to support career growth. In order for the process of professional development of managers to be of high quality, a methodology is being developed based on the characteristic and relevant knowledge of adult education. Central to this process is proper planning, timing and flow between learning new information, practice and evaluating the improvement process. A manager's career vision is the most important part of a leadership development plan. This will set the general tone for the professional development strategies that the manager must implement. He needs to rethink what he really wants to achieve in his professional life. Internal motivators for managers’ self-growth play an important role in this re-evaluation process.